Effect Difference of Centella asiatica Leaves Methanolic Extract on Scratch and Incision of Dimethylbenz [A] Anthracene (DMBA) Induced Dysplasia Incidence - Ahyar Riza; Denny Satria; Nurhalijah; Illuh Wulandani (TALENTA, 2023)
Oral epithelial dysplasia is an abnormal cytology and architectural change that can develop into oral malignancy with a high mortality rate. Centella asiatica leaves possesses the potential to act as a chemopreventive agent and is known for its relative safety and ease of obtainability. Therefore, this study aimed to determine effect of Centella asiatica leaves extract on dysplasia induced by dimethylbenz [a] anthracene (DMBA) with scratch and incision. The in vivo study involved 21 Wistar rats (Rattus novergicus) divided into three groups. The groups received 2% Centella asiatica leaves methanolic extract orally by force-feeding once daily, from day 1 until day 61. At day 29, dysplasia was induced by scratching the buccal mucosa of each rat using a syringe containing 0.5% DMBA. This was conducted with incision 1 cm in length and half angle in depth, 1 cm in length and 1 mm in depth, and 2 cm in length and 1 mm in depth for groups 1, 2, and 3. Furthermore, the rats were sacrificed, and histopathological analysis was performed using hematoxylin-eosin staining. The degree of dysplasia was assessed using the WHO 2017 classification, and the data were analyzed using the Mann-Whitney test. Meanwhile, the statistical test showed significant difference in the degree of dysplasia for all groups. It can be concluded that Centella asiatica methanolic extract leaves possesses the potential to be a chemopreventive agent in reducing dysplasia levels.